Follistatin‐like protein 1 modulates IL‐17 signaling via IL‐17RC regulation in stromal cells. Issue 8 (9th May 2017) - Campfield, Brian T; Eddens, Taylor; Henkel, Matthew; Majewski, Martin; Horne, William; Chaly, Yury; Gaffen, Sarah L; Hirsch, Raphael; Kolls, Jay K
Abstract : Follistatin‐like protein 1 (FSTL‐1) possesses several newly identified roles in mammalian biology, including interleukin (IL)‐17‐driven inflammation, though the mechanism underlying FSTL‐1 influence on IL‐17‐mediated cytokine production is unknown. Using parallel in vitro bone marrow stromal cell models of FSTL‐1 suppression, we employed unbiased microarray analysis to identify FSTL‐1‐regulated genes and pathways that could influence IL‐17‐dependent production of IL‐6 and granulocyte colony‐stimulating factor. We discovered that FSTL‐1 modulates Il17rc gene expression. Specifically, FSTL‐1 was necessary for Il17rc gene transcription, IL‐17RC surface protein expression and IL‐17‐dependent cytokine production. This work identifies a mechanism by which FSTL‐1 influences IL‐17‐driven inflammatory signaling in vitro and reveals a novel function for FSTL‐1, as a modulator of gene expression. Thus enhanced understanding of the interplay between FSTL‐1 and IL‐17‐mediated inflammation may provide insight into potential therapeutic targets of IL‐17‐mediated diseases and warrants ongoing study of in vivo models and clinical scenarios of FSTL‐1‐influenced diseases.